Elaborately Engineering a Self‐Indicating Dual‐Drug Nanoassembly for Site‐Specific Photothermal‐Potentiated Thrombus Penetration and Thrombolysis. Issue 4 (21st November 2021) - Zhao, Zhiqiang; Zhang, Xuanbo; Zhang, Hongyuan; Shan, Xinzhu; Bai, Meiyu; Wang, Zhe; Yang, Fujun; Zhang, Haotian; Kan, Qiming; Sun, Bingjun; Sun, Jin; He, Zhonggui; et al.
Abstract: Thrombotic cardio‐cerebrovascular diseases seriously threaten human health. Currently, conventional thrombolytic treatments are challenged by the low utilization, inferior thrombus penetration, and high off‐target bleeding risks of most thrombolytic drugs, resulting in unsatisfactory treatment outcomes. Herein, it is proposed that these challenges can be overcome by precisely integrating the conventional thrombolytic strategy with photothermal therapy. After co‐assembly engineering optimization, a fibrin‐targeting peptide‐decorated nanoassembly of DiR (a photothermal probe) and ticagrelor (TGL, an antiplatelet drug) is prepared for thrombus‐homing delivery, abbreviated as FT‐DT NPs. The elaborately engineered nanoassembly shows multiple advantages, including simple preparation with high drug co‐loading capacity, synchronous delivery of two drugs with long systemic circulation, thrombus‐targeted accumulation with self‐indicating function, as well as photothermal‐potentiated thrombus penetration and thrombolysis with high therapeutic efficacy. As expected, FT‐DT NPs not only show bright fluorescence signals in the embolized vessels, but also perform photothermal/antiplatelet synergistic thrombolysis in vivo. This study offers a simple and versatile co‐delivery nanoplatform for imaging‐guided photothermal/antiplatelet dual‐modality thrombolysis. Abstract : To achieve site‐specific photothermal‐potentiated thrombus penetration and thrombolysis, a carrier‐free nanoassembly is self‐aggregated by DiR and TGL. The dual‐drug nanoassembly demonstrates multiple advantages, including simple preparation with high drug co‐loading capacity, synchronous co‐delivery with long systemic circulation, thrombus‐targeted accumulation with self‐indicating function, as well as photothermal‐potentiated thrombus penetration and thrombolysis with high security.